Effects of Different Pollen Substitute Diets on the Survival Rate and Diet Preference of Foraging Honey Bees (Apis mellifera L.) - Nigam, Yashvi; Rana, Amber; James, Barish E. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Honey bee is an eusocial insect from class Insecta. The potential for thriving honey bee colonies hinges on the availability of an effective pollen substitute, particularly during periods of scarcity when natural pollen supply is limited. Numerous beekeepers provide their bees with various pollen substitutes to ensure they receive adequate nutrition during periods of insufficient pollen quantity or quality. For Methodology transparent boxes were made and each artificial diet were kept in each box for each ten replicas of Honey Bees. The experiment was based on Artificial diets as pollen substitutes. For experiment Honey Bee, Apis mellifera was taken and feed with five different diets and data was analysed with test significance level is 0.001.